Egypt's new urban communities. Investigating the policy, design and management of smart growth. The cases of Heliopolis-Cairo and New Aswan-Aswan. - Alhowaily, Anas (My University, 2020)
Erforscht werden die Erfahrungen in Vergangenheit und Gegenwart in zwei Abschnitten der modernen Geschichte Ägyptens, vor und nach der Einführung des Programms für Neue Städte, bezeichnet als prä-NUCP und NUCP. Die Forschung legt die Grundlage mit einer systematischen Literaturstudie über die Entwicklung der institutionellen und legislativen Rahmenbedingungen in beiden Zeitabschnitten und führt dafür zwei repräsentative Fallstudien durch, Heliopolis-Kairo und Assuan-Neu Assuan. Gewählt wird ein induktives Vorgehen, das unterschiedliche methodische Ansätze kombiniert: Datenerhebung, Analyse archivierter Daten und Karten, ortsbezogene Interviews sowie fotografische und kartografische Aufnahmen.

This research seeks out how to contribute to reforming the Egyptian policy, management, and design of urban growth in desert areas for achieving Smart Growth. It investigates past and pre-sent experiences over two eras throughout the modern Egyptian history, before and after the initiation of the New Urban Communities Program (pre-NUCP and NUCP). The research under-takes a systematic literature review to the development of the institutional and legislative setup governing both eras along with investigating two representative case studies in retrospect, Heliopolis-Cairo and New Aswan-Aswan. An inductive research approach is adopted using different research methods including, data mining, analysis of archival data, maps, local interviews, photographs, and mapping.
Keywords: Stadtplanung; Planungsgeschichte; Urbanisierung; Stadtwachstum; Verstädterungsprozess; Prozesssteuerung; Wüste; Bebauungsdichte; Siedlungsdichte; Neue Stadt; Fehlentwicklung; Nachhaltigkeit; Fallstudie; Smartes Wachstum